ANALYSIS OF DIALOGUES DURING A MEETING AT BALINESE TRADITIONAL COMMUNITY’S HALL (BANJAR) FROM SOCIOLINGUISTICS POINT OF VIEW - I Komang Sumaryana Putra (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Most of Balinese people are bound with their social life and have a close relationship among others. They are being bound to the village traditions and determined by their bound to their residence as well as to the organization named Banjar. Banjar is also a place where Balinese people mingle and conduct a traditional meeting. The conversation was held when people were doing discussion in a social meeting. The topic was about ritual ceremonies which spend a lot of money and this meeting led by Kelian Banjar (Leader of Banjar). The data was collected by using observational method by note taking and emphasizing the important points, i.e. the choice was made on the priority based on the frequency of the conversation done by the people. From the conversation, the role of language in society can be observed in the context of situation; in this case: ‘in-group language’. We can observe a meaning deviance in first session when the explanation of Kelian was interrupted by the first participant and the second participant. Beside that, two languages were used in conversation, and show us that code-switching occurs in this conversation. The reason of code-switching usage in conversation above is that because those participants lack of ability in one language when talking about a particular topic. They switched when they could not find an appropriate word or expression or when the language being used does not have the items or appropriate translations for the vocabulary needed.